Complementation of reducing power for 5-hydroxyvaleric acid and 1,5-pentanediol production via glucose dehydrogenase in Escherichia coli whole-cell system - Kim, Byungchan; Oh, Suk Jin; Hwang, Jeong Hyeon; Kim, Hyun Jin; Shin, Nara; Joo, Jeong Chan; Choi, Kwon Young; Park, See Hyoung; Park, Kyungmoon; Bhatia, Shashi Kant; Yang, Yung Hun (Enzyme and Microbial Technology, 2023)
One of the key intermediates, 5-hydroxyvaleric acid (5-HV), is used in the synthesis of polyhydroxyalkanoate monomer, δ-valerolactone, 1,5-pentanediol (1,5-PDO), and many other substances. Due to global environmental problems, eco-friendly bio-based synthesis of various platform chemicals and key intermediates are socially required, but few previous studies on 5-HV biosynthesis have been conducted. To establish a sustainable bioprocess for 5-HV production, we introduced gabT encoding 4-aminobutyrate aminotransferase and yqhD encoding alcohol dehydrogenase to produce 5-HV from 5-aminovaleric acid (5-AVA), through glutarate semialdehyde in Escherichia coli whole-cell reaction. As, high reducing power is required to produce high concentrations of 5-HV, we newly introduced glucose dehydrogenase (GDH) for NADPH regeneration system from Bacillus subtilis 168. By applying GDH with D-glucose and optimizing the parameters, 5-HV conversion rate from 5-AVA increased from 47% (w/o GDH) to 82% when using 200 mM (23.4 g/L) of 5-AVA. Also, it reached 56% conversion in 2 h, showing 56 mM/h (6.547 g/L/h) productivity from 200 mM 5-AVA, finally reaching 350 mM (41 g/L) and 14.6 mM/h (1.708 g/L/h) productivity at 24 h when 1 M (117.15 g/L) 5-AVA was used. When the whole-cell system with GDH was expanded to produce 1,5-PDO, its production was also increased 5-fold. Considering that 5-HV and 1,5-PDO production depends heavily on the reducing power of the cells, we successfully achieved a significant increase in 5-HV and 1,5-PDO production using GDH.
Keywords: 1,5-pentanediol; 5-hydroxyvaleric acid; Cell system; Encodings; Glucose dehydrogenase; Recombinant E coli; Recombinant E. coli; Reducing power; Whole cell; Whole-cell biocatalysis; Escherichia coli; Glucose 1-Dehydrogenase; Valerates; 1,5-pentanediol; 5-hydroxyvaleric acid; Glucose dehydrogenase; Recombinant E. coli; Whole-cell biocatalysis